CONSTITUTIONS OF THE RUSSIAN FEDERATION REPUBLICS: BASIC FEATURES AND PROBLEMS OF DEVELOPMENT - S. S. Yagudin (Russian Journal of Economics and Law)
Objective: to analyze the existing constitutions of the Russian Federation republics, to identify their main features and problems of development. Methods: formal-logical, comparative legal. Results: Basing on the analysis of the constitutions of all the Russian Federation republics, the main features are identified that reflect the identity and traditions of multinational republics’ statehood; the increasing role of constitutions in the progressive development of the national republics is shown. The author's definition of the constitution of the republic is proposed; the degree of autonomy and full state power of the Russian Federation subjects are disclosed, including the subjects within the republics’ jurisdiction. Scientific novelty: for the first time the main features of the republics’ constitutions are disclosed in comparative terms, as well as their their essence and content; it is proposed to extend the legal regulation variability of federal relations, to consolidate all republics’ jurisdiction directly in their constitutions; the conclusion is made about the necessity of full implementation of the constitutional provisions and further development of the republics’ constitutions. Practical value: the conclusions and recommendations formulated in the study can be used in scientific, legislative and educational activities for the further improvement of federal relations and practices of constitutional development in the republics.